Numerical Study of Two-Phase Flow in Centrifugal Dust Collectors - Kamol Akhrarovich Adylov; Rozhkova Elena Vladimirovna; Mengliev Ismoil Abdunazar ugli (International Journal on Orange Technologies, 2022)
In this article, a numerical study of a turbulent swirling air flow with solid particles in a centrifugal dust collector is carried out. A modified Spalart-Almaras turbulence model (SARC) was used to compile the mathematical model and the interaction between solid particles and air mass was taken into account. The Lagrangian approach was used to study the trajectory of solid particles.